Enhancing Competitiveness through Marketing Strategy Optimization and Product Innovation: Evidence from Choco Bakery - Khairunnisa Nasution; Hanny Fadillah; Fathul Arzaq (Yayasan Bayt Shufiya Nusantara, 2025)
This study analyzes the marketing strategies and product innovations implemented by Choco Bakery as part of its efforts to strengthen competitiveness in the bakery industry. Established in 2020 in the post-pandemic era, Choco Bakery has demonstrated notable growth by adopting product differentiation strategies such as the use of premium chocolate ingredients and the introduction of unique flavor variations. In addition, the bakery has effectively utilized digital marketing channels, including social media platforms and online delivery applications, to broaden its market reach and engage consumers more interactively. The research adopts a mini-research method, with data collected through interviews and direct observation of the bakery's operational activities. The findings reveal that innovation driven by customer feedback, multi-channel promotional efforts, and consistent product quality play a central role in enhancing customer satisfaction and loyalty. Furthermore, the study emphasizes that continuous monitoring of market trends and consumer preferences contributes to Choco Bakery's adaptability and sustained market relevance. Based on the results, this study recommends future development strategies, including expanding seasonal and limited-edition product lines, strengthening brand storytelling, and increasing strategic partnerships with local suppliers and digital platforms to ensure long-term business growth.